Molecular identification of Polyporales sp. isolated from a rare lung fungal infection case in Malaysia - Zainulabid, Ummu Afeera; Abdul Azih, Muhammad Naimmuddin; Abd. Fuaat, Azliana; Kamarudin, Norhidayah; Abidin, Mohd Radhwan; Soffian, Sharmeen Nellissa; Ahmad, Hajar Fauzan (2021)
Fungal infection is rarely reported in immunocompetent retroviral disease patients. We report a first case of a 42-year-old man with underlying retroviral disease on Highly Active Antiretroviral Therapy (HAART) who was infected with pulmonary Polyporales sp. Despite undetected viral load with high CD4 count, the patient was found to have unexplained significant loss of weight and appetite. Subsequently, CT thorax revealed multiple lung nodules at the lateral segment of the right middle lobe of lung. Bronchoscopy was carried out and showed a black patch at the right bronchus intermedius, lateral segment of the middle lobe which did not disappear upon bronchial flush or wash. The fungal culture was first described as Cladosporium sp. based on colony appearance and morphology under light microscopy examination. Due to the rarity of this infection, we recovered the sample from paraffin embedded tissue block and then re-cultured on Sabouraud agar at 30 Celcius. The total genomic DNA was then extracted by using the DNeasy Blood and Tissue kit. Full-length genome sequencing was carried out using Minion Oxford Nanopore Technology platform using long read protocols which resulted as Polyporales sp. This finding will definitely add a novel value for precision diagnosis and clinical surveillance of a rare fungal infection.